0
Upcoming SlideShare
×

Thanks for flagging this SlideShare!

Oops! An error has occurred.

×
Saving this for later? Get the SlideShare app to save on your phone or tablet. Read anywhere, anytime – even offline.
Standard text messaging rates apply

# Slide subtopic 5

180

Published on

0 Likes
Statistics
Notes
• Full Name
Comment goes here.

Are you sure you want to Yes No
• Be the first to comment

• Be the first to like this

Views
Total Views
180
On Slideshare
0
From Embeds
0
Number of Embeds
0
Actions
Shares
0
3
0
Likes
0
Embeds 0
No embeds

No notes for slide

### Transcript

• 1. UNIVERSITI PENDIDKAN SULTAN IDRIS PREPARED BY : MOHAMAD AL FAIZ BIN SELAMAT
• 2. &#xF07D; Principle of Induction. To prove that P (n) is true for all positive integers n, where P (n) is a propositional function. A proof by mathematical induction has two parts:&#xF07D; Basic step: We verify that P (1) is true.&#xF07D; Inductive step: We show that the conditional proposition &#x2200; k &#x2208; , P (k) &#x21D2; P (k + 1) is true.
• 3. Prove for &#x2265; 1&#xF07D; 1 x 1! + 2 x 2! + 3 x 3! + ... + n x n! = (n + 1)! - 1This could be also written by using &#x2211; notation
• 4. ProofBase case: n + 1The left hand side is 1x1! The right hand side is2! - 1. They are equal.Inductive hypothesis: Suppose this holds
• 5. &#xF07D; We need to prove&#xF07D; Consider the left hand side= (n+1)! &#x2013; 1 + (n+1) x (n+1)= (n+1)! (1+n+1) -1 = (n+2)! -1
• 6. &#xF07D; We can picture each proposition as a domino: P (k)
• 7. P (0) P (1) P (2) P (k) P (k+1) &#x2026;..
• 8. P (0) P (1) P (2) P (k) P (k+1) &#x2026;..
• 9. P (1) P (2) P (k) P (k+1) &#x2026;..
• 10. P (2) P (k) P (k+1) &#x2026;..
• 11. P (k) P (k+1)&#x2026;..
• 12. P (k) P (k+1)&#x2026;..
• 13. P (k+1)&#x2026;..
• 14. Then, &#x2200; n P (n) is true.Use induction to prove that the sum of the first nodd integers isBase case (n=1): the sum of the first 1 odd integerisAssume p (k): the sum of the first k odd integersis Yeah!Where, 1 + 3 + &#x2026; + (2k+1) = =1Prove that 1 + 3 + &#x2026; + + (2k-1) + (2k+1) = 1 + 3 + &#x2026; + + (2k-1) + (2k+1) = =
• 15. Prove that: 1 x 1! + 2 x 2! + &#x2026; + n x n! = (n+1)! -1, &#x2200; nBase case (n=1): 1 x 1! = (1 x 1)! -1?Assume P (k 1 x 1! + 2 x 2! + &#x2026; + k x k! = (k+1)! -1Prove that: x 1! + 2 x 2! + &#x2026; + k x k! + (k+1) (k+1)! = (k+2)! -1 1 x 1! + 2 x 2! + &#x2026; + k x k! + (k+1) (k+1)! = (k+1)! -1+ (k+1) (k+1) = (1 + (k+1)) (k+1)! &#x2013; 1 = (k+2) (k+1)! -1 = (k+2)! - 1 1 x 1! = 1 2! &#x2013; 1 = 1